Functional range of motion in the upper extremity and trunk joints: Nine functional everyday tasks with inertial sensors - Doğan, Mert; Koçak, Mertcan; Onursal Kılınç, Özge; Ayvat, Fatma; Sütçü, Gülşah; Ayvat, Ender; Kılınç, Muhammed; Ünver, Özgür; Aksu Yıldırım, Sibel (Gait & posture, 2019)
•Most of functional activities requires maximum 24° flexion in wrist.•Requirements of bilateral activities were found similiar in both extremities.•Flexion of the trunk joints less than 30° for many activities. Functional range of motion is defined as the required range of motions for individuals to maintain maximal independence, along with optimal conditions for activities of daily living. Intervention plans for rehabilitation are directed towards the acquisition of anatomical range of motion. However, this isn’t always possible based on person’s etiology, prognosis, or severity of disease. The aim of this study is to determine functional range of motion during different unilateral, bilateral symmetrical and bimanual asymmetrical tasks of activities of daily living. Participants completed nine basic activities of daily living (hand to head, hanging jacket, eating, wallet placement to back pocket, washing hands and face, removing belt, water pouring, brushing teeth) linked according to International Classification of Functioning, Disability and Health, while joint kinematics of the trunk and upper extremity were recorded with inertial measurement units. Peak values of mean joint angles were determined for each activities of daily living. MVN BIOMECH Awinda MTW2-3A7G6 sensors (Xsens Technologies B.V. Enschede, Netherlands) were used for 3D kinematic analysis of activities. Forty-six healthy subjects (right-dominant) were included in this study. Range of motion requirements of all activities were defined 37.85° extension, 91.18° flexion, 1.25° adduction, 39.45° abduction, 63.6° internal rotation, 21.8° external rotation in the dominant shoulder, 124.17° flexion in the dominant elbow, 40.29° extension, 23.66° flexion, 18.31° supination, 12.56° pronation, 18.27 ulnar deviation and, 18.36° radial deviation in the dominant wrist. Maximum trunk range of motions were found to be 29.75° flexion in C7-T1, 10.74° flexion in T12-L1, and 24.16° flexion in L5-S1. It is thought that the results of this research will contribute to the determination of normative data needed for surgical interventions, technological rehabilitation devices and task-spesific rehabilitation programs which based patient's motor skill level.